HUBUNGAN PENGETAHUAN GIZI DENGAN KADAR GULA DARAH PENDERITA DIABETES MELLITUS TIPE II DI POLI DEWASA WILAYAH KERJA UPT BLUD PUSKESMAS SALO - RIZKI RAHMAWATI LESTARI; ZURRAHMI ZR (Jurnal Ners, 2022)
Diabetes mellitus (DM) is a collection of symptoms that arise in a person due to the body experiencing disturbances in controlling blood sugar levels. These disorders can be caused by inadequate insulin secretion, impaired insulin function (insulin resistance) or a combination of both. The purpose of this study was to determine the relationship between nutritional knowledge and blood sugar levels in patients with type II diabetes at the Internal Medicine Clinic at the Salo Health Center in 2021. This study was a quantitative analytical study with a cross-sectional approach involving 44 respondents of patients with type II diabetes. using simple random sampling. This study was conducted on 18-22 December 2021. The data collection technique used a questionnaire and measured blood sugar levels with GCU. Data analysis used univariate analysis and bivariate analysis with fisher's exact test. The results showed that the nutritional knowledge variable was obtained (p = 0.001), so it was concluded that there was a significant relationship with the blood sugar levels of respondents with Diabetes Mellitus in the Adult Poly Health Center Salo in 2021.